Rare-earth-induced peroxo-phosphotungstates: Enhanced proton conductivity in corresponding membranes - Qianqian Shang; Keqin Shen; Dongyan Zhao; Xiaoyue Wang; Yuting Wei; Haiying Wang; Guan Wang; Dongdi Zhang; Jingyang Niu (Polyoxometalates)
Two rare-earth-induced peroxo-polyoxotungstates (peroxo-POTs), namely, two-dimensional [Ln2(H2O)4(OH)P2W6(O2)4O23]3− (2D-Ln2, Ln = Pr, Sm) and one-dimensional [Ln(H2O)4P4W6(O2)6(OH)4O24]5− (1D-Ln, Ln = Gd, Tb, Dy, Ho), were successfully prepared by similar synthesis methods based on that used to synthesize {P3W6(O2)6} clusters. However, although the original {P3W6(O2)6} building block remained, a completely new structure was achieved in these two lanthanide-based peroxo-POT derivatives that was induced by the rare-earth cations. 2D-Ln2 was composed of {P2W6(O2)4} polyanion units linked by replacing {PW3(O2)3} with {PW3(O2)2}, while 1D-Ln was composed of two symmetric {P2W3(O2)3} cores connected by rare-earth cations. Furthermore, the proton conductivities of 2D-Ln2 and 1D-Ln were investigated. At 65 °C and 95% relative humidity (RH), 2D-Pr2 and 1D-Tb exhibited conductivities of 2.62 × 10−3 and 2.78 × 10−3 S∙cm−1, respectively, while the conductivities of their corresponding Nafion membranes were considerably higher, with values of 1.65 × 10−1 and 1.44 × 10−1 S∙cm−1, respectively, under the same conditions.